Perspectives on the physics of hypernuclei - Feliciello, A (AIP conference proceedings, 2009)
The imminent commissioning of the Japan Proton Accelerator Research Complex (J-PARC) and the planned construction of the Facility for Antiproton and Ion Research (FAIR) will offer the opportunity to pursue a systematic program of high-precision and high-statistics studies in the field of hypernuclear physics. This subject will represent as well an important topic in the physics program approved for the upgraded Continuous Electron Beam Accelerator Facility (CEBAF) at the Thomas Jefferson National Accelerator Facility (JLab).A survey of the future experimental initiatives is presented, with particular emphasis on the activities that will be carried out by Italian and Japanese researchers.